Answer:
<h2>
The desired equation is y = (4/3)x - 14/3.</h2>
Step-by-step explanation:
This new line passes thru (-4, 8) and (0, 5).
As we move from (-4, 8) to (0, 5), x increases by 4 and y decreases by 3.
Thus, the slope of this line is m = rise / run = -3/4.
Thus, the slope of a line perpendicular to the given line is the negative reciprocal of -3/4: 4/3.
Thus, the equation of a line perpendicular to the given line is
y = (4/3)x + b.
This line passes thru the point (5, 2). Thus, the following is true:
2 = (4/3)(5) + b, or 2 = 20/3 + b
Mult. this 2 by 3/3, we get 6/3, so that 6/3 = 20/3 + b. b = -14/3.
<h2>
The desired equation is y = (4/3)x - 14/3.</h2>